2004
DOI: 10.1002/jcc.20087
|View full text |Cite
|
Sign up to set email alerts
|

Energetic and topological analysis of the reaction of Mo and Mo2 with NH3, C2H2, and C2H4 molecules

Abstract: The Density functional theory has been applied to characterize the structural features of Mo(1,2)-NH(3),-C(2)H(4), and -C(2)H(2) compounds. Coordination modes, geometrical structures, and binding energies have been calculated for several spin multiplets. It has been shown that in contrast to the conserved spin cases (Mo(1,2)-NH(3)), the interaction between Mo (or Mo(2)) and C(2)H(4) (or C(2)H(2)) are the low-spin (Mo-C(2)H(4) and -C(2)H(2)) and high-spin (Mo(2)-C(2)H(4) and -C(2)H(2)) complexes. In the ground … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…In a previous article,13 we have already checked the reliability of the level of theory employed in the present work by studying the bare molybdenum atom and dimer. For the energetic gap between the first excited state ( 5 S ( d 5 s 1 )) and the ground state ( 7 S ( d 5 s 1 )) of Mo, the PW91PW91/LANL2DZ level of theory is the one that better reproduce the measured value (1.38, 1.45, 1.42, and 1.33 eV, the PW91PW91,13 CI,37 BPW91,38 and experimental39 values, respectively).…”
Section: Computational Detailsmentioning
confidence: 95%
See 1 more Smart Citation
“…In a previous article,13 we have already checked the reliability of the level of theory employed in the present work by studying the bare molybdenum atom and dimer. For the energetic gap between the first excited state ( 5 S ( d 5 s 1 )) and the ground state ( 7 S ( d 5 s 1 )) of Mo, the PW91PW91/LANL2DZ level of theory is the one that better reproduce the measured value (1.38, 1.45, 1.42, and 1.33 eV, the PW91PW91,13 CI,37 BPW91,38 and experimental39 values, respectively).…”
Section: Computational Detailsmentioning
confidence: 95%
“…In a recent work,13 we have presented an energetic and topological study of the adduct formation process for the interaction of Mo and Mo 2 with different small ligands, namely NH 3 , C 2 H 2 , and C 2 H 4 . We have shown that Mo and Mo 2 essentially interact with C 2 H 2 and C 2 H 4 via an electron pair transfer from the metallic‐center to the ligand, forming a chemical bond with the carbon atoms, while the interaction between Mo (or Mo 2 ) and NH 3 has mostly an electrostatic character.…”
Section: Introductionmentioning
confidence: 99%
“…BET [37] has been applied to different elementary reactions as proton transfers [36,58], isomerisations [59], electron transfers [60] and studies on two-state reactivity [61][62][63]. A systematic investigation of the mechanism of important organic reactions such as the Diels-Alder reactions [45,46] the 1,3-dipolar reaction between fulminic acid and acetylene [44], the molecular mechanism of the Bergman cyclization [64], the trimerization of acetylene [65] the "chameleonic vs centauric" mechanisms of the Cope rearrangement of 1,5 hexadiene and its cyano derivatives [66] the Nazarov cyclization [67] and the S N 2 reaction [68].…”
Section: Topological Analysis Of Elf and Catas-trophe Theorymentioning
confidence: 99%
“…The ELF topology has been extensively used for study of chemical bonding , aromaticity problems [81][82][83][84][85][86][87][88], reactivity [89][90][91], and chemical reactions [92][93][94][95][96][97][98][99][100][101][102][103][104][105]. Several review papers have already been published [86,[106][107][108].…”
Section: Concepts From the Elf Topologymentioning
confidence: 99%